Group portrait of six women - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows a group portrait of six women. The woman second from the left is holding a small dog in her arms. The third woman from the right is holding a pool cue. A poster of Joan Baez's Noel album cover hangs on the wall behind them.